Vitamin D deficiency as a public health issue: using vitamin D2 or vitamin D3 in future fortification strategies - Wilson, Louise R.; Tripkovic, Laura; Hart, Kathryn H.; Lanham-New, Susan A (Proceedings of the Nutrition Society, 2017)
The role of vitamin D in supporting the growth and maintenance of the skeleton is robust; with recent research also suggesting a beneficial link between vitamin D and other non-skeletal health outcomes, including immune function, cardiovascular health and cancer. Despite this, vitamin D deficiency remains a global public health issue, with a renewed focus in the UK following the publication of Public Health England's new Dietary Vitamin D Requirements. Natural sources of vitamin D (dietary and UVB exposure) are limited, and thus mechanisms are needed to allow individuals to achieve the new dietary recommendations. Mandatory or voluntary vitamin D food fortification may be one of the mechanisms to increase dietary vitamin D intakes and subsequently improve vitamin D status. However, for the food industry and public to make informed decisions, clarity is needed as to whether vitamins D2 and D3 are equally effective at raising total 25-hydroxyvitamin D (25(OH)D) concentrations as the evidence thus far is inconsistent. This review summarises the evidence to date behind the comparative efficacy of vitamins D2 and D3 at raising 25(OH)D concentrations, and the potential role of vitamin D food fortification as a public health policy to support attainment of dietary recommendations in the UK. The comparative efficacy of vitamins D2 and D3 has been investigated in several intervention trials, with most indicating that vitamin D3 is more effective at raising 25(OH)D concentrations. However, flaws in study designs (predominantly under powering) mean there remains a need for a large, robust randomised-controlled trial to provide conclusive evidence, which the future publication of the D2–D3 Study should provide (BBSRC DRINC funded: BB/I006192/1). This review also highlights outstanding questions and gaps in the research that need to be addressed to ensure the most efficacious and safe vitamin D food fortification practices are put in place. This further research, alongside cost, availability and ethical considerations (vitamin D3 is not suitable for vegans), will be instrumental in supporting government, decision-makers, industry and consumers in making informed choices about potential future vitamin D policy and practice.